Calypso - Memorial University of Newfoundland. Extension Service (Producer) (MUN Extension Service, 1978)
Calypso is a work oriented rehabilitation centre in Lewisporte. It trains mentally handicapped adults to be productive members of the work force. Interviews with Rupert Short, Allister Mesh, and Josephine O'Rourke.